PENGARUH VARIASI DEBIT ALIRAN DAN PIPA ISAP (SECTION) TERHADAP KARAKTERISTIK POMPA SENTRIFUGAL YANG DIOPERASIKAN SECARA PARALEL - ., Supardi; Renwarin, Max Millian (MEKANIKA: Jurnal Teknik Mesin, 2015)
The pump is a machine used to raise the liquid from the surface of the low to the higher, or move the fluidfrom the high pressure. Plan and create a means of centrifugal pumps for water flow to the arrangement / circuitParallel to the needs of fluid mechanics lab in August 17, 1945 the University of Surabaya. Step experiment with agate valve openings 900, 700, 500, 350, with a maximum rotation 2580 RPM pump, get the planning andcharacteristics (Head, Capacity) of the two pumps are arranged in parallel. The influence of the suction pipediameter variations on these tests affect the capacity (Q). The larger the diameter of the suction pipe is used, thegreater the capacity of the water produced. The influence of variations in flow through the valve opening effect onHead (H). the smaller the aperture setting, the valve resulting Head Small increasingly.Keywords: Centrifugal Pumps, Suction Pipe, Valves, Head and capacity.